Pembuatan Aplikasi Web Desa Wisata Cipayung Depok - Frendiana, Viving; Utami, Budi; Widhiantoro, Dandun; Wagyana, Agus; Fathurahman, Mohamad; Zulhelman (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2024)
The rapid development of digital technology has affected many sectors, including the tourism sector. Utilizing digital platforms, such as websites, is an option for promoting tourist areas. Kampung Setaman is an area that has the potential to become an educational tourism destination. However, this village does not yet have a website as a promotional medium for its village. Therefore, this research aims to develop a website for the Kampung Setaman Tourism Village which is expected to help the Kampung Setaman management in promoting the area more widely. Creating a website begins with a needs analysis to find out what menus need to be on the website. Next, the website interface was designed using HTML, CSS, Javascript and PHP, as well as creating a database using MySQL. Collecting and creating website content in the form of writing, photos and videos about the area and programs of Kampung Setaman is also carried out to then be uploaded on the website being developed. The final stage of creating a website is testing performance efficiency and security. Based on performance efficiency testing, an average performance value of 90.2% was obtained. Meanwhile, from security testing using HostedScan, it was found that website security was quite good.